Новые находки арабских дирхемов в Тамбовской области - Андреев, С.И.; Лебедев, В.П.; Пачкалов, A.B. (Степи Европы в эпоху средневековья, 2009)
Over 30 numismatic artifacts have been found by now on the territory of the upper reaches of the Tsna, Moksha, and Sura rivers populated by the Mordva-Moksha tribes in the 7th - 11th centuries. These include 1 hoard containing over 16 silver al-Kufa coins (11 of which have been defined) and 23 individual finds. 5 dirhems of the 1st third of the 10th century and 6 its imitations have been defined in the hoard.